Effects of systemic pretreatment with the NAALADase inhibitor 2-PMPA on oral methamphetamine reinforcement in C57BL/6J mice - Fultz, Elissa K.; Nei, Andrea Y. T.; Chi, Joyce C.; Lichter, Jacqueline N.; Szumlinski, Karen K. (Frontiers in Psychiatry, 2024)
Introduction Repeated exposure to methamphetamine (MA) in laboratory rodents induces a sensitization of glutamate release within the corticoaccumbens pathway that drives both the rewarding and reinforcing properties of this highly addictive drug. Such findings argue the potential for pharmaceutical agents inhibiting glutamate release or its postsynaptic actions at glutamate receptors as treatment strategies for MA use disorder. One compound that may accomplish both of these pharmacological actions is the N-acetylated-alpha-linked-acidic dipeptidase (NAALADase) inhibitor 2-(phosphonomethyl)pentanedioic acid (2-PMPA). 2-PMPA elevates brain levels of the endogenous agonist of glutamate mGluR3 autoreceptors, N-acetyl-aspartatylglutamate (NAAG), while potentially acting as an NMDA glutamate receptor antagonist. Of relevance to treating psychomotor stimulant use disorders, 2-PMPA is reported to reduce indices of both cocaine and synthetic cathinone reward, as well as cocaine reinforcement in preclinical rodent studies. Method Herein, we conducted three experiments to pilot the effects of systemic pretreatment with 2-PMPA (0-100 mg/kg, IP) on oral MA self-administration in C57BL/6J mice. The first experiment employed female mice with a prolonged history of MA exposure, while the mice in the second (females) and third (males and females) experiment were MA-naïve prior to study. In all experiments, mice were trained daily to nose-poke for delivery of unadulterated MA solutions until responding stabilized. Then, mice were pretreated with 2-PMPA prior to operant-conditioning sessions in which nose-poking behavior was reinforced by delivery of 120 mg/L or 200 mg/L MA (respectively, in Experiments 1 and 2/3). Results Contrary to our expectations, 30 mg/kg 2-PMPA pretreatment altered neither appetitive nor consummatory measures related to MA self-administration. In Experiment 3, 100 mg/kg 2-PMPA reduced responding in the MA-reinforced hole, as well as the number of reinforcers earned, but did not significantly lower drug intake. Discussion These results provide mixed evidenced related to the efficacy of this NAALADase inhibitor for reducing oral MA reinforcement in female mice.